Superparamagnetic Iron Oxide Nanoparticle-Mediated Forces Enhance the Migration of Schwann Cells Across the Astrocyte-Schwann Cell Boundary In vitro - Huang, Liangliang; Xia, Bing; Liu, Zhongyang; Cao, Quanliang; Huang, Jinghui; Luo, Zhuojing (Frontiers in Cellular Neuroscience, 2017)
Schwann cells (SCs) are one of the most promising cellular candidates for the treatment of spinal cord injury. However, SCs show poor migratory ability within the astrocyte-rich central nervous system (CNS) environment and exhibit only limited integration with host astrocytes. Our strategy for improving the therapeutic potential of SCs was to magnetically drive SCs to migrate across the astrocyte-SC boundary to intermingle with astrocytes. SCs were firstly magnetized with poly-L-lysine-coated superparamagnetic iron oxide nanoparticles (SPIONs). Internalization of SPIONs showed no effect upon the migration of SCs in the absence of a magnetic field (MF). In contrast, magnetized SCs exhibited enhanced migration along the direction of force in the presence of a MF. An inverted coverslip assay showed that a greater number of magnetized SCs migrated longer distances onto astrocytic monolayers under the force of a MF compared to other test groups. More importantly, a confrontation assay demonstrated that magnetized SCs intermingled with astrocytes under an applied MF. Furthermore, inhibition of integrin activation reduced the migration of magnetized SCs within an astrocyte-rich environment under an applied MF. Thus, SPION-mediated forces could act as powerful stimulants to enhance the migration of SCs across the astrocyte-SC boundary, via integrin-mediated mechanotransduction, and could represent a vital way of improving the therapeutic potential of SCs for spinal cord injuries.